Temporal changes in intensity of bird parasite infections are dependent on latitude in the Western Palearctic - Møller, Anders Pape; Merino, Santiago; Soler, Juan José; Adriaensen, Frank; Cantarero, Alejandro; Eeva, Tapio; Figuerola, Jordi; García-del, Río Marina; Garrido-Bautista, Jorge; Heylen, Dieter; Marzal, Alfonso; Matthysen, Erik; et al. (Public Library of Science (PLoS), 2026)
In this study we compare the intensity and prevalence of parasites and reproductive parameters across 14 bird populations sampled in two different seasons separated by approximately 10 years apart, in the Western Palearctic, to test for climate-parasite associations. Overall, 9 different bird species and 62 different host-parasite interactions were studied. We found non-significant trends between the two sampling years in terms of reduced clutch and brood size. However, we observed a decrease in population size between the sampling years, while differences in laying date were negatively related to temperature change between the years. Feather parasites and non-dipteran parasites tended to decrease in both prevalence and intensity, while dipteran parasites showed a few changes with time between the two sampling periods. The prevalence of blood parasites showed a non-significant increase between the two years studied. Importantly, the magnitude and even the direction of the temporal changes in parasitism experienced by different host species across populations depended on latitude, with the northernmost populations showing the smallest decrease in parasite intensity. In addition, changes in temperature between the two study periods decreased with latitude. These results, therefore, point to a potential effect of climate change on the incidence of parasitic diseases, but with variable magnitude and direction across a latitudinal gradient in Europe.